Labor market impacts of eco-development initiatives in protected areas - Balietti, Anca; Jaiswal, Sreeja; Schäffer, Daniel (Journal of environmental economics and management, 2024)
Eco-development seeks to balance economic development with biodiversity conservation, enhancing the effectiveness of protected area management. This paper examines the labor market impacts of eco-development initiatives implemented in the protected areas of the Western Ghats, India, a significant biodiversity hotspot facing intense socio-economic pressures. Our findings show that eco-development has substantially altered labor market outcomes in villages within and surrounding protected areas, resulting in a higher share of non-farm employment. This shift is marked by a reduction in year-round work and an increase in seasonal employment. These effects appear to stem from the specific types of jobs created by eco-development and the changes in land use patterns it promotes, such as a higher proportion of forested land and increased reliance on rainfed agriculture over irrigated farming. Descriptive evidence also suggests that, despite improvements in literacy, the affected villages experience lower consumption levels and higher poverty rates.